Ophiotholia (Echinodermata: Ophiuroidea): A little-known deep-sea genus present in polymetallic nodule fields with the description of a new species - Eichsteller, Angelina; Martynov, Alexander; O’Hara, Timothy D.; Christodoulou, Magdalini; Korshunova, Tatiana; Bribiesca-Contreras, Guadalupe; Martinez Arbizu, Pedro (Frontiers in Marine Science, 2023)
Introduction The Clarion Clipperton Zone (CCZ) in the Northeast Pacific Ocean holds the largest deposits of polymetallic nodules at abyssal depths. These nodules are rock formations containing valuable metals and minerals targeted for mining. They further provide diverse habitat for a range of deep-sea species. Little is known so far on the taxonomy, natural history and biogeography of these deep-sea animals which is vital for accurate assessment of the risk of species extinctions from large-scale mining. One of the most abundant megafaunal groups in the CCZ is the Ophiuroidea (brittle stars), of which Ophiotholia is one of the more abundant genera found in the area. The genus Ophiotholia has a world-wide distribution and currently holds six species. Methods Material collected from seven scientific cruises to the CCZ was examined, morphologically, together with comparative material from all the known species. The small size and the damage caused during sampling often impeded their identification. The specimens were also genetically analyzed using a fragment of the mitochondrial COI gene. Scanning Electron Microscope images of the key microstructural characters were made using selected specimens from CCZ as well as from the comparative material. Result and discussion One morphotype was identified as the known species Ophiotholia supplicans Lyman, 1880, while the second is new to science and is described in this paper. The umbrella spines and the arrangement of their articulations on the lateral arm plate, were selected as the most relevant morphological characters in the taxonomy of the genus Ophiotholia and a revised identification key of all characters from all known Ophiotholia species is provided as a table in the supplement material. The identification and description of such a little-known genus improves the evaluation of the biodiversity not only in the CCZ but also for the deep sea.